RITUAL â€œKLIWONANâ€ BAGI MASYARAKAT BATANG - Widyatwati, Ken (HUMANIKA, 2014)
The narrative have a meaning and structure. The structure of kliwonan myth is representation form the society, who to support. Structure or model to become representation from the society to exist in stage unconscious, and only to be looking for with structuralism Levi-Straus Analysis. Kliwonan Ritual for Batang Society is a folklore wich Batang society. Kliwonan Ritual is not ritual content, but it have many contents be trusted by community, The aim of this research is description of kliwonan Ritual for Batang Society are component Identification, and the content of myth. This Ritual perform every Jumat Kliwon day in Javanese Callender. Time is 14.00-18.00 am. The place is Alun-alun Batang, Central Java. The content of Exorcism Ritual for Batang Society is place, time, instrument, ritual offering, prayer and myth. This myth is jumat kliwon and kliwonan Ritual..